γ-Radiation Induces Leaf Trichome Formation in Arabidopsis - Nagata, Toshifumi (American Society of Plant Physiologists, 1999)
We observed induction of additional trichome formation on the adaxial surface of mature leaves of Arabidopsis after massive doses (1–3 kilograys) of γ-radiation from cobalt-60. A typical increase in trichome number was observed in the seventh leaf when the full expansion of the fifth leaf was irradiated. Under normal growth conditions, trichome numbers on the adaxial surface of seventh leaf of the Arabidopsis ecotypes Columbia (Col) and Landsberg erecta (Ler) were 122.5 ± 22.7 and 57.5 ± 14.5, respectively. However, γ-radiation induced additional trichome formation and the numbers rose to 207.9 ± 43.7 and 95.0 ± 27.1 in Col and Ler, respectively. In Col the shape of new trichomes was intact and their formation was spatially maintained at equal distances from other trichomes. In Ler trichome morphology was aberrant and the formation was relatively random. Treatment with antioxidants before γ-irradiation suppressed the increase in trichome number, and treatment with methyl viologen and light induced small trichomes. These results suggest that γ-radiation-induced trichome formation is mediated by active oxygen species generated by water radiolysis. γ-Radiation-induced trichome formation was blocked in the trichome mutants ttg-1, gl1-1, and gl2-1. These results suggest that γ-radiation-induced trichome formation is mediated by the normal trichome developmental pathway.